Preoperative sense of coherence associated with the 10-year outcomes of lumbar spinal stenosis surgery. (June 2019) - Sinikallio, Sanna; Pakarinen, Maarit; Tuomainen, Iina; Airaksinen, Olavi; Viinamäki, Heimo; Aalto, Timo J
A prospective 10-year follow-up study was conducted to determine the significance of the preoperative sense of coherence, with respect to the preoperative and 10-year clinical characteristics, among lumbar spinal stenosis patients ( N  = 99). In addition, the predictive value of the preoperative sense of coherence regarding the 10-year surgery outcome was also evaluated. In a logistic regression analysis, a weak preoperative sense of coherence and low functional ability predicted the patients' functional ability 10 years after the surgery. Moreover, those patients with weak sense of coherence before surgery showed poorer functional ability 10 years after the surgery, but not preoperatively. A weak preoperative sense of coherence seems to associate with poorer long-term outcome after surgery; therefore, various rehabilitation strategies are discussed.